Clinical characteristics and pathogen spectra of parasitic infections in a tertiary hospital of Shanghai: A 13-year retrospective study - Zhang, Jinming; Xu, Jing; Tang, Weiliang; Mo, Ruidong; Shang, Dabao; Lu, Jie; Li, Ziqiang; Wang, Xiaolin; Shi, Dongmei; Xie, Qing; Xiang, Xiaogang (Frontiers in Public Health, 2022)
Background This study performed a follow-up investigation of parasitic infections and the evolution of the infection spectra in Shanghai and its surrounding areas in Eastern China. The current study was conducted in the Shanghai Ruijin Hospital, a tertiary hospital affiliated with Shanghai Jiao Tong University School of Medicine. Methods This retrospective investigation reviewed a total of 412 parasitic infections in patients admitted to the Department of Infectious Diseases, Ruijin Hospital from January 1, 2010 to July 31, 2022. Detailed information for these patients was retrieved from the Electronic Medical Record System. Analysis was performed using GraphPad Prism 5.0 and SPSS Statistics 26. Results Overall, 17 species of parasites were detected from the 412 admissions. Over the 13 years, the number of patients peaked in 2021 and food-born parasites (FBPs) were the primary species. During the most recent 5 years, Clonorchis sinensis, replacing Paragonimus westermani, has become the primary parasite detected among the patients, consistent with the observation that eating uncooked fish has turned into the most common route of transmission. Paragonimus westermani infections declined with age, but Cysticercus increased with age. The periods from the onset of symptoms to definite diagnosis for some patients infected with Sparganum mansoni, Paragonimus westermani, and Cysticercus were more than 6 months. Interestingly, eosinophilia was only detected in 51.83% of parasite-infected patients. In addition, superinfections of parasites were common in our study. Conclusion Our study demonstrates the transitional change in the prevalence of parasitic infection over the latest 13 years in a single center in Eastern China. The incidence of parasitic infections peaked in 2021, and the dominant parasitic species switched from a soil origin to foodborne. The direction for the diagnosis and prevention of parasitic infection among different age groups should alter according to age. It is difficult to diagnose parasitic infections and superinfections that occur in some patients. Thus, more sensitive and efficient detection methods should be developed. In addition, although eosinophilia and elevated IgE are still reliable indicators for initiating screening of parasitic infection, the development of novel parasitic diagnostic kits is still in urgent need for occult infection.